Method for preparing nano calcium carbonate from ardealite

By using complexing agents or chelating agents as phase transfer agents on phosphogypsum, combined with carbonization precipitation method and crystal form control agents, the problem of difficulty in efficient preparation of nano calcium carbonate on industrial scale in the prior art is solved, and efficient and controllable preparation of nano calcium carbonate is achieved, thereby enhancing the added value of phosphogypsum.

CN119774648APending Publication Date: 2025-04-08合肥中亚环保科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820879.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently prepare high-purity and uniform particle size nano calcium carbonate on the industrial scale, and the added value of the comprehensive utilization of phosphogypsum is relatively low.

Method used

Nanocalcium carbonate is prepared under the action of crystal form control agent by using phosphogypsum as raw material, complexing agent or chelating agent as phase transfer agent, combined with carbonization precipitation method. The method includes phase transfer reaction, aging separation reaction and carbonization precipitation reaction, which improves production efficiency and reduces costs by recycling the phase transfer agent.

Benefits of technology

The preparation of nano calcium carbonate with controllable process conditions, high production efficiency, uniform product particle size and good dispersion is achieved, which increases the added value of phosphogypsum and meets the requirements of industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774648A_ABST
    Figure CN119774648A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nano calcium carbonate from ardealite, which comprises the following steps: S1, mixing ardealite with a phase transfer agent solution, stirring to fully react, and filtering to obtain a phase transfer solution; s2, performing stirring reaction on the phase transfer liquid, performing solid-liquid separation on a product, collecting an obtained first precipitate for later use, separating out the phase transfer agent in filtrate, and returning to the step S1 for recycling; s3, deionized water, ammonia water and a crystal form control agent are added into the first precipitate obtained in the step S2, a carbonized precipitate raw material solution containing calcium ions is obtained, a reaction is carried out under the stirring condition while a carbonization agent is introduced, when the pH value reaches 7.5-9.0, the reaction is finished, solid-liquid separation is carried out on a product, the phase transfer agent in filtrate is separated, and the mixture returns to the step S1 to be recycled; and washing and drying the obtained second precipitate to obtain the nano calcium carbonate. According to the method, the industrial solid waste ardealite is used as the raw material, waste resources are fully utilized, the process conditions are controllable, the nano calcium carbonate is efficiently prepared, and the obtained nano calcium carbonate is uniform in particle size and good in dispersity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of industrial solid waste resource recycling, and in particular to a method for preparing nano calcium carbonate from phosphogypsum. Background Art

[0002] Nano-CaCO3 is widely used as an inorganic filler in rubber, plastic, coating, papermaking and other industries due to its obvious advantages in reinforcement, transparency and dispersibility. With the rapid development of rubber, plastic and other industries, the demand for nano-calcium carbonate has increased rapidly, and higher requirements have been put forward for the performance indicators of nano-calcium carbonate such as particle size and oil absorption value. Therefore, the preparation of ultra-fine, uniform particle size and high activity nano-calcium carbonate has become a research hotspot.

[0003] The solid waste residue formed by a small amount of undissolved phosphate rock and by-product calcium sulfate dihydrate (CaSO4·2H2O) in the wet phosphoric acid process is called phosphogypsum. Therefore, whether the comprehensive utilization and industrialization of phosphogypsum can be realized directly affects the sustainable development of the phosphate fertilizer industry.

[0004] At present, phosphogypsum is mainly used in the field of building materials (such as road base materials, building material additives, etc.), agricultural fields (soil conditioners and fertilizers, etc.); in the chemical industry, it is used to prepare cement clinker and co-produce H2SO4, prepare potassium sulfate and calcium nitrate, prepare light CaCO3, etc. But overall, the product has low added value and is not very technologically advanced.

[0005] The preparation of nano-CaCO3 mainly includes Ca(OH)2-H2O-CO2, Ca 2+ -H2O-CO2 two types of reaction systems, in which Ca 2+ -H2O-CO2 reaction system can produce nano-CaCO3 products with high purity and uniform particle size. However, due to the extremely fast reaction speed of this system and the difficulty in controlling the process conditions, it can only be produced at a low initial Ca 2+ Concentration (about 0.1 mol·L -1 ) is not convenient for industrial-scale production. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing nano-calcium carbonate from phosphogypsum, aiming to provide a method for preparing nano-calcium carbonate efficiently by using industrial solid waste phosphogypsum as raw material, making full use of waste resources, and controllable process conditions. The prepared nano-calcium carbonate has uniform particle size and good dispersibility.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention discloses a method for preparing nano-CaCO3 using phosphogypsum as a raw material, comprising the following steps:

[0009] S1, mixing phosphogypsum and phase transfer agent solution, stirring to fully react, and filtering to obtain a phase transfer liquid (the main component is CaY solution);

[0010] S2, stirring the phase transfer liquid to react, separating the product into solid and liquid, collecting the obtained first precipitate for standby use, separating the phase transfer agent in the filtrate and returning it to step S1 for repeated use;

[0011] S3, adding deionized water, ammonia water and a crystal control agent to the first precipitate obtained in step S2 to obtain a carbonized precipitation raw material liquid containing calcium ions, reacting under stirring conditions while introducing a carbonizing agent, and ending the reaction when the pH value reaches 7.5-9.0, separating the product into solid and liquid, and returning the phase transfer agent in the separated filtrate to step S1 for repeated use, and washing and drying the obtained second precipitate to obtain nano calcium carbonate.

[0012] Further: Step S1 is a phase transfer reaction stage. The phosphogypsum is pre-treated to remove soluble impurities, and the main component is CaSO4·2H2O, with a dry content of 70-90%. The phase transfer agent is Ca 2+ complexing agent or chelating agent.

[0013] Step S2 is the aging and separation reaction stage. The main component of the first precipitate is CaY, and the main component of the filtrate is an aqueous solution of NH4Y and (NH4)2SO4. After membrane separation, NH4Y is returned to the phase transfer reaction step S1 for recycling, and the (NH4)2SO4 solution can be used to produce (NH4)2SO4 as a by-product.

[0014] Step S3 is the carbonization precipitation reaction stage. 2+ Concentration is 0.8~1.5mol.L -1 The main component of the filtrate is the phase transfer agent NH4Y, which is returned to step S1 for recycling. (According to the law of conservation of mass, the Ca in the carbonized precipitated raw material liquid is 2+ The theoretical yield of nano-CaCO3 that can be obtained through all precipitation is used as the calculation basis to calculate the addition amount of component 1 and component 2 of the crystal shape control agent);

[0015] The present invention uses phosphogypsum as raw material, a complexing agent or a chelating agent as a phase transfer agent, extracts the Ca element in the phosphogypsum, and adopts a carbonization precipitation method under the action of a crystal control agent to prepare high-quality nano-CaCO3 with a small particle size (30 to 50 nm), uniform particle size and good dispersibility.

[0016] As a further solution of the present invention: in step S1, the concentration of the phase transfer agent solution is 1 to 3 mol·L -1 ;

[0017] As a further solution of the present invention: the molar ratio of CaSO4·2H2O to the phase transfer agent in the phosphogypsum is 2:3 to 6:3.

[0018] As a further scheme of the present invention: in step S1, the phase transfer agent is one or two of citric acid and its salts, glucose and its salts, ammonium formate, ammonium acetate, ammonium propionate, ammonium chloride, ammonium alginate, ammonium salicylate and diammonium phosphate; preferably, the phase transfer agent is NH4Y, i.e. ammonium citrate.

[0019] As a further solution of the present invention: in step S1, the reaction time is 10 to 100 minutes, and the reaction temperature is 5 to 35°C.

[0020] As a further solution of the present invention: in step S2, the reaction time is 1 to 4 hours, and the reaction temperature is 35 to 95°C.

[0021] As a further scheme of the present invention: in step S3, the crystal form controller includes component one and component two, component one of the crystal form controller is any one of sucrose, salicylic acid, ethanolamine, sodium silicate, ammonium succinate, polyethylene glycol, polyacrylamide, sodium polyacrylate, phenylalanine, and sodium carboxymethyl cellulose, and component two is any one of sodium oleate, sodium tripolyphosphate, tetrabutyl titanate, sodium dodecyl sulfate, disodium ethylenediaminetetraacetate, and hydroxyethyl dimethacrylate.

[0022] As a further solution of the present invention: the addition amount of the component one and the component two is based on the Ca in the carbonization precipitation raw material solution. 2+ The theoretical amount of nano-CaCO3 that can be obtained by all precipitation is used as a reference, and the addition amount of the component one is 0.5-1.5%, and the addition amount of the component two is 0.5-1.5%.

[0023] As a further solution of the present invention: in step S3, the stirring rate is 200-600 rpm, and the reaction temperature is 5-35°C.

[0024] As a further solution of the present invention: in step S3, the nano-CaCO3 is a pure phase calcite crystal, the average particle size of the nano-CaCO3 is 30-50 nm, and the specific surface area of ​​the nano-CaCO3 is 20-35 m 2 ·g -1 The oil absorption value of the nano-CaCO3 is 35-40 g·g -1The main performance indicators are better than the technical indicators of type II nano-CaCO3 for rubber in "Nano Calcium Carbonate" (GB / T19590-2023).

[0025] As a further solution of the present invention: in step S3, the flow rate of the carbonizing agent (CO2) is 0.1 to 0.6 L·min -1 .

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) Compared with the existing nano-CaCO3 preparation process, the present invention adopts phosphogypsum as raw material, uses a complexing agent or a chelating agent as a phase transfer agent, and adds an appropriate amount of a crystal shape control agent to prepare nano-CaCO3 with an average particle size of 30 to 50 nm, which is conducive to the development of high value-added products of phosphogypsum; and the CaY concentration in the reaction system is relatively high (about 1 mol·L -1 ), with higher production efficiency.

[0028] (2) The phase transfer agent selected in the present invention includes one or two of citric acid and its salts, glucose and its salts, ammonium formate, ammonium acetate, ammonium propionate, ammonium chloride, ammonium alginate, ammonium salicylate and ammonium dihydrogen phosphate, which can be well combined with Ca 2+ Complexation or chelation is carried out so that the Ca element in phosphogypsum can be extracted to a greater extent. In addition, this process adopts a circulating process and makes full use of phase transfer agents, which greatly reduces production costs.

[0029] (3) After the phase transfer liquid prepared in step 1 is aged, CaY precipitation is easily precipitated, and the CaY precipitation filter cake obtained in step 2 is used as the calcium source for the carbonization precipitation reaction in step 3, with an initial Ca 2+ The concentration is easy to control while ensuring the purity of the product.

[0030] (4) The crystal shape control agent used in the present invention includes component one and component two, wherein component one is one of sucrose, salicylic acid, ethanolamine, sodium silicate, ammonium succinate, polyethylene glycol, polyacrylamide, sodium polyacrylate, phenylalanine, and sodium carboxymethyl cellulose, and component two is one of sodium oleate, sodium tripolyphosphate, tetrabutyl titanate, sodium dodecyl sulfate, disodium ethylenediaminetetraacetate, and hydroxyethyl dimethacrylate, which can effectively inhibit the growth of CaCO3 particles, and the prepared nano-CaCO3 has a small particle size, uniform particle size, and good dispersibility.

[0031] (5) The present invention also has the advantages of mild process conditions and green environmental protection. The process uses industrial waste gas CO2 as a carbonizing agent, "treating waste with waste and turning waste into treasure", which meets the requirements of economic circular development. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1This is a schematic diagram of the process for preparing active nano-calcium carbonate from phosphogypsum.

[0033] Figure 2 This is the SEM image of the nano-CaCO3 product prepared in Example 1.

[0034] Figure 3 This is the XRD diagram of the nano-CaCO3 product prepared in Example 1.

[0035] Figure 4 This is the SEM image of the nano-CaCO3 product prepared in Example 2.

[0036] Figure 5 This is the SEM image of the nano-CaCO3 product prepared in Example 3.

[0037] Figure 6 This is the SEM image of the nano-CaCO3 product prepared in Example 4.

[0038] Figure 7 This is the SEM image of the nano-CaCO3 product prepared in Example 5.

[0039] Figure 8 This is the SEM image of the nano-CaCO3 product prepared in Comparative Example 1.

[0040] Fig. 9 This is the SEM image of the nano-CaCO3 product prepared in Comparative Example 2.

[0041] Fig.10 This is the SEM image of the nano-CaCO3 product prepared in Comparative Example 3.

[0042] Fig.11 This is the SEM image of the nano-CaCO3 product prepared in Comparative Example 4. DETAILED DESCRIPTION

[0043] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0045] All materials are commercially available conventional products. "Parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0046] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0047] Example 1

[0048] Step A: Prepare 1.5 mol.L -1 100 mL of the phase transfer agent NH4Y solution is measured and placed in a beaker, and 21.52 g of phosphogypsum (the phosphogypsum used contains 90% CaSO4·2H2O, and the feeding molar ratio is 4:3) is added. The reaction is stirred at 5°C and 300 rpm for 30 min, and the insoluble impurities (main components are phosphoric acid and phosphates, fluorides, etc.) in the reaction solution are removed by suction. The filtrate obtained is the phase transfer liquid; the phase transfer rate of the prepared phase transfer liquid is 91.88% after testing.

[0049] Step B, the phase transfer liquid is aged in a constant temperature water bath at 80°C and 300rpm for 2h, and the filter cake obtained by filtration is CaY precipitate (for standby use). The main components of the filtrate are NH4Y and (NH4)2SO4 aqueous solution. After membrane separation, the NH4Y solution can be returned to the phase transfer reaction for recycling; the precipitation rate of the prepared CaY was tested to be 89.58%.

[0050] Step C: Take 54.19 g of the filter cake obtained above and add it to 41.38 mL of deionized water, add 0.125 g of sodium polyacrylate, 0.075 g of sodium dodecyl sulfate and 18.75 mL of ammonia water, mix well (control the initial Ca 2+ The concentration is 1 mol·L -1 ), at a carbonization reaction temperature of 15°C, a stirring rate of 400 rpm, and a CO2 flow rate of 0.3 L min -1 CO2 was introduced under the experimental conditions to react until the pH value was 7.80. After the reaction, the solid-liquid separation was performed by filtration. The main component of the filtrate was the phase transfer agent NH4Y, which was returned to the phase transfer reaction for recycling. The filter cake was washed and dried to obtain a nano-CaCO3 sample. Figure 2 As shown, the average particle size of the prepared nano-CaCO3 particles is 35nm. Figure 3 It can be seen that the nano-CaCO3 sample prepared in Example 1 is a pure phase calcite type.

[0051] Example 2

[0052] Proceed according to the method of Example 1, except that:

[0053] Step A: The phase transfer reaction time is 10 min. The phase transfer rate of the prepared phase transfer liquid is 94.91% after testing.

[0054] Step B: The aging time is 2.5 hours. The precipitation rate of the prepared CaY is 92.03%.

[0055] Step C: Add 0.125 g of sodium polyacrylate and 0.1 g of sodium dodecyl sulfate into the carbonization reactor.

[0056] Depend on Figure 4 It can be seen that the average particle size of the prepared nano-CaCO3 particles is 40nm.

[0057] Example 3

[0058] Proceed according to the method of Example 1, except that:

[0059] Step A: The temperature of the constant temperature water bath is 10° C. The phase transfer rate of the prepared phase transfer liquid is 94.7%.

[0060] Step B: The aging temperature is 90° C. The precipitation rate of the prepared CaY is 90.12% after testing.

[0061] Step C: The carbonization reaction temperature is 20°C.

[0062] Depend on Figure 5 It can be seen that the average particle size of the prepared nano-CaCO3 particles is 50nm.

[0063] Example 4

[0064] Proceed according to the method of Example 1, except that:

[0065] Step A: Add 28.70 g of phosphogypsum (the phosphogypsum used contains 90% CaSO4·2H2O, and the feeding molar ratio is 3:3). The phase transfer rate of the prepared phase transfer liquid is 68.92% after testing.

[0066] Step B is the same as in Example 1.

[0067] Step C, CO2 flow rate is 0.35L·min -1 ,Depend on Figure 6 It can be seen that the average particle size of the prepared nano-CaCO3 particles is 45nm.

[0068] Example 5

[0069] Proceed according to the method of Example 1, except that:

[0070] Step A: 17.22 g of phosphogypsum (phosphogypsum used contains 90% CaSO4·2H2O, and the feeding molar ratio is 5:3) is added. The phase transfer rate of the prepared phase transfer liquid is 89.97% after testing.

[0071] Step B is the same as in Example 1.

[0072] Step C: Add 0.15g of component one polyacrylamide and 0.075g of component sodium dodecyl sulfate to the carbonization reactor. Figure 7 It can be seen that the average particle size of the prepared nano-CaCO3 particles is 50nm.

[0073] Comparative Example 1

[0074] Proceed according to the method of Example 2, except that:

[0075] The crystal form controlling agent in step C is 0.3 g of sodium tripolyphosphate.

[0076] like Figure 8 As shown, the average particle size of the prepared nano-CaCO3 particles was detected to be 150 nm.

[0077] Comparative Example 2

[0078] Proceed according to the method of Example 2, except that:

[0079] In step C, no crystal control agent is added.

[0080] like Fig. 9 As shown, the average particle size of the prepared nano-CaCO3 particles was detected to be 125 nm.

[0081] Comparative Example 3

[0082] Proceed according to the method of Example 2, except that:

[0083] In step C, no sodium lauryl sulfate was added.

[0084] like Fig.10 As shown, the average particle size of the prepared nano-CaCO3 particles was detected to be 80 nm.

[0085] Comparative Example 4

[0086] Proceed according to the method of Example 2, except that:

[0087] In step C, no sodium polyacrylate is added.

[0088] like Fig.11 As shown, the average particle size of the prepared nano-CaCO3 particles was detected to be 70 nm.

[0089] By comparing Example 2 with Comparative Examples 2-4, it can be seen that component one and component two in the crystal form control agent have a synergistic effect. Adding them simultaneously can well control the average particle size and crystal form of the nano-CaCO3 particles. When one of them is added alone, the particle size of the CaCO3 particles is larger and the crystal morphology is irregular.

[0090] By comparing Examples 1-5 with Comparative Example 1, it can be seen that the crystal form control agent used in the examples has good particle size control effect and uniqueness. When the crystal form control agent used in Comparative Example 1 is added, although the particle morphology becomes regular and close to spherical, the particle size increases relatively.

[0091] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0092] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A method for preparing nano calcium carbonate from phosphogypsum, characterized in that: The following steps are involved: S1, mixing phosphogypsum and a phase transfer agent solution, stirring to fully react, and filtering to obtain a phase transfer liquid; S2, stirring the phase transfer liquid to react, separating the product into solid and liquid, collecting the obtained first precipitate for standby use, separating the phase transfer agent in the filtrate and returning it to step S1 for repeated use; S3, adding deionized water, ammonia water and a crystal control agent to the first precipitate obtained in step S2 to obtain a carbonized precipitation raw material liquid containing calcium ions, reacting under stirring conditions while introducing a carbonizing agent, and ending the reaction when the pH value reaches 7.5-9.0, separating the product into solid and liquid, and returning the phase transfer agent in the separated filtrate to step S1 for repeated use, and washing and drying the obtained second precipitate to obtain nano calcium carbonate.

2. The preparation method according to claim 1, characterized in that: In step S1, the Ca of the phase transfer solution 2+ Concentration is 1~3mol.L -1 .

3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of CaSO4·2H2O to the phase transfer agent in the phosphogypsum is 2:3 to 6:

3.

4. The preparation method according to claim 1, characterized in that: The phase transfer agent is at least one of citric acid and its salts, glucose and its salts, ammonium formate, ammonium acetate, ammonium propionate, ammonium chloride, ammonium alginate, ammonium salicylate and diammonium phosphate.

5. The preparation method according to claim 1, characterized in that: In step S1, the reaction time is 10 to 100 minutes, and the reaction temperature is 5 to 35°C.

6. The preparation method according to claim 1, characterized in that: In step S2, the reaction time is 1 to 4 hours, and the reaction temperature is 35 to 95°C.

7. The preparation method according to claim 1, characterized in that: In step S3, the crystal shape control agent is mixed by component one and component two, wherein component one is any one of sucrose, salicylic acid, ethanolamine, sodium silicate, ammonium succinate, polyethylene glycol, polyacrylamide, sodium polyacrylate, phenylalanine, and sodium carboxymethyl cellulose, and component two is any one of sodium oleate, sodium tripolyphosphate, tetrabutyl titanate, sodium dodecyl sulfate, disodium ethylenediaminetetraacetate, and hydroxyethyl dimethacrylate; And / or: the addition amount of the component one is 0.5-1.5w% of the theoretical calculated value of the second precipitate, and the addition amount of the component two is 0.5-1.5w% of the theoretical calculated value of the second precipitate.

8. The preparation method according to claim 1, characterized in that: In step S3, the calcium ion concentration is 0.8 to 1.5 mol.L -1 .

9. The preparation method according to claim 1, characterized in that: In step S3, the stirring rate is 200-600 rpm, and the reaction temperature is 5-35°C; in step S3, the carbonizing agent is carbon dioxide, and its flow rate is 0.1-0.6 L.min -1 .

10. A nano calcium carbonate prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The nano calcium carbonate is a pure phase calcite crystal, with an average particle size of 30 to 50 nm and a specific surface area of ​​20 to 35 m 2 .g -1 , oil absorption value is 35~40g.g -1 .